ER bodies in plants of the Brassicales order: biogenesis and association with innate immunity - Nakano, Ryohei T.; Yamada, Kenji; Bednarek, Paweł; Nishimura, Mikio; Hara-Nishimura, Ikuko (Frontiers in Plant Science, 2014)
The endoplasmic reticulum (ER) forms highly organised network structures composed of tubules and cisternae. Many plant species develop additional ER-derived structures, most of which are specific for certain groups of species. In particular, a rod-shaped structure designated as the ER body is produced by plants of the Brassicales order, which includes Arabidopsis thaliana. Genetic analyses and characterisation of A. thaliana mutants possessing a disorganised ER morphology or lacking ER bodies have provided insights into the highly organised mechanisms responsible for the formation of these unique ER structures. The accumulation of proteins specific for the ER body within the ER plays an important role in the formation of ER bodies. However, a mutant that exhibits morphological defects of both the ER and ER bodies has not been identified. This suggests that plants in the Brassicales order have evolved novel mechanisms for the development of this unique organelle, which are distinct from those used to maintain generic ER structures. In A. thaliana, ER bodies are ubiquitous in seedlings and roots, but rare in rosette leaves. Wounding of rosette leaves induces de novo formation of ER bodies, suggesting that these structures are associated with resistance against pathogens and/or herbivores. ER bodies accumulate a large amount of β-glucosidases, which can produce substances that potentially protect against invading pests. Biochemical studies have determined that the enzymatic activities of these β-glucosidases are enhanced during cell collapse. These results suggest that ER bodies are involved in plant immunity, although there is no direct evidence of this. In this review, we provide recent perspectives of ER and ER body formation in A. thaliana, and discuss clues for the functions of ER bodies. We highlight defence strategies against biotic stress that are unique for the Brassicales order, and discuss how ER structures could contribute to these strategies.